The Vo2Max Ability of Men's Football Basketball Athletes, with the Extreme Club Men's Basketball Athlete - Oktavianus, Irfan; Marta, Ibnu Andli; Mariati, Sari (Jurnal Guru Peneliti Professional, 2017)
This research comes from the reality in the field, the low achievement of men's basketball athletes in Club Extreme City of Solok. This can be caused by many things, one of which is the Athlete's VO2 Max ability. Then the male basketball athletes of FIK UNP in this study were used as a measure of the above abilities aimed at proving the level of VO2 Max in basketball. This type of research is descriptive. The population of FIK UNP athletes and the Extreme Club of Solok City was 22 samples. Each athlete was taken 11 people per club, research sites at FIK UNP and at SMAN 1 Kota Solok. The research was carried out on 30 November to 30 December 2016. All populations were sampled using the total sampling technique. Instrumentation for data collection through the VO2 Max test using a multi-stage test (Bleep Test). The question posed is how high is the VO2 Max ability of FIK UNP men's basketball athletes, then how high is the VO2 Max ability of the Extreme basketball club athletes in Solok City. Data were analyzed using frequency tabulation. . Judging from the data frequency distribution of VO2Max, FIK UNP athletes who have very good VO2Max are 1 person, both 8 people, while 2 people are less and there are not really enough. being 2 people, less than 8 people and absolutely none